Fostering Informed Decisions: Impact of a Decision Aid Among Men Registered to Undergo Mass Screening for Prostate Cancer in a Randomized Controlled Trial - Williams, Randi M. (2013)
OBJECTIVE: Screening asymptomatic men for prostate cancer is controversial and informed decision making is recommended. Within two prostate cancer screening programs, we evaluated the impact of a print-based decision aid (DA) on decision-making outcomes. METHODS: Men (N=543) were 54.9 (SD=8.1) years old and 61% were African-American. The 2 (booklet type: DA vs. usual care (UC)) × 2 (delivery mode: Home vs. Clinic) randomized controlled trial assessed decisional and screening outcomes at baseline, two-months, and 13-months. RESULTS: Intention-to-treat linear regression analyses using generalized estimating equations revealed that DA participants reported improved knowledge relative to UC (B=.41, p<.05). For decisional conflict, per-protocol analyses revealed a group by time interaction (B = −.69, p<.05), indicating that DA participants were less likely to report decisional conflict at two-months compared to UC participants (OR=.49, 95% CI: .26–.91, p<.05). CONCLUSION: This is the first randomized trial to evaluate a DA in the context of free mass screening, a challenging setting in which to make an informed decision. The DA was highly utilized by participants, improved knowledge and reduced decisional conflict. PRACTICE IMPLICATIONS: These results are valuable in understanding ways to improve the decisions of men who seek screening and can be easily implemented within many settings.